South Africa’s State and Business Governance of Public Private Partnerships for Provision of Services and Infrastructure: A Case of Gauteng E-Tolls - Ramoroka, T. M. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
The aim of the paper is to demonstrate that whilst the intersection of governance of the state and business in Public Private Partnerships (PPP) is meant to deliver efficient and reliable public services and infrastructure, it also conveniently serves the selfish interests of the two parties. Typically, a PPP involves parallel fragmentary existence of monostatic and adaptive governance, wherein the former serves state interests while the latter fulfils business commercial motives. In the process of the monostatic governance serving bureaucratic interests of the state and the adaptive allowing for unfettered financial and commercial transactions, society’s social good remain circumvented. The paper uses Gauteng freeway e-tolls to demonstrate that notwithstanding the apparent societal resistance of the system, as evidence through the ballot-box reaction against the African National Congress (ANC) during the 2016 municipal elections, the state and business have stood firm in their collusion to sustain the initial intension. Hence, the recent assessment of impact which has provided evidence of the deleterious effects did little to sway the original decision of e-tolling. Therefore, the paper concludes that the state’s insistence on e-tolling and bureaucratic repression of societal interests is a function of the imperatives to service business’ financial and commercial gates at the expense of tax paying public.
Journal article published in International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Gauteng freeway e-tolling; Governance; Public Private Partnerships; State; Public administration; Payment in lieu taxes